Human Resource Management - The Case of the X Footwear Company - Nguyễn, Ngọc Thắng (Đại học Kinh tế, 2016)
The leather and footwear industry in Vietnam is currently faced with a shortage of human resources - HR. Therefore, HR competition inside the industry is vigorous. The most important task of managers is how to appeal to talented, skilled workers and limit the number of skilled workers leaving companies to work for competitors. In order to appeal to and maintain talented people, companies should pay more attention to reward policies as well as motivation policies for them. This research focuses on the case study at the X Footwear Company, based on studying the human resource management - HRM of the company. A questionnaire was designed to collect data related to HRM from employees.